MORAL VALUES AND ETHICS IN A CHILDREN’S PICTURE BOOK “OF THEE IS SING: A LETTER TO MY DAUGHTERS” BY BARACK OBAMA - Feti Kaniasari; Gustaman Saragih (Universitas Indraprasta PGRI, 2019)
The purpose of this study was to analyze: 1) Moral values in a children’s picture book